Determinasi Kepuasan Tamu melalui Kebersihan Kamar dan Kualitas Layanan Housekeeping pada Hotel Luxury Resort di Jepang - Slamet Slamet; Henry Yuliamir (Mahesa Research Center, 2026)
This study aims to analyze the influence of room cleanliness and perceived quality of housekeeping services on guest satisfaction at The Windsor Hotel TOYA Resort & Spa, Japan. The study used a quantitative approach with a survey method. Data were collected through a structured questionnaire from 120 hotel guests selected using purposive sampling techniques, then analyzed using multiple linear regression. The results showed that room cleanliness and perceived quality of housekeeping services had a positive and significant effect on guest satisfaction, both partially and simultaneously (p < 0.05). Partially, perceived quality of housekeeping services had a more dominant influence than room cleanliness, as indicated by a larger regression coefficient value. These findings indicate that aspects of the service process and the quality of housekeeping staff interactions play a key role in shaping guest satisfaction at luxury resort hotels. The implications of this study emphasize the importance of consistent room cleanliness management and improving the quality of housekeeping services based on Japanese service culture as a strategy to increase hotel satisfaction and competitiveness sustainably.